Evaluation of two premedication protocols in Cats (Xylazine - Tramadol vs Xylazine - Buprenorphine) - Paredes-Carvajal, Pamela; Segnini-Herrera, Gilberto; Castillo-Hidalgo, Edy Paul (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The feline patients are becoming more and more representative in the clinic. Therefore, they deserve proper management during their visit by avoiding as much as possible generating stress, contemplating if the feline is very fearful or aggressive when using chemical restraints to safeguard the safety of the medical team and to shorten times in procedures that are required to be performed. The main objective of this research was to evaluate two pharmacological combinations as premedication protocols: (xylazine 0.5 mg·kg-1 - tramadol 2 mg·kg-1) in comparison with (xylazine 0.5 mg·kg-1 - buprenorphine 0.03 mg·kg-1) in 12 young cats between 6 and 18 months old, all considered clinically healthy and in need of short procedures. Their cardiovascular (heart rate and blood pressure), respiratory (pulse oximetry and respiratory rate) and thermoregulatory (rectal temperature) effects were evaluated before the application and consecutively every 5 minutes (min) until recovery, together with the degree of sedation and muscle relaxation provided by these drugs to each patient, using the Ramsay scale at 20 min. On the other hand, the analgesic effect was evaluated by using the Feline Grimace Scale in two times, before applying the pharmacological combinations and at 20 min. The results did not show significant differences (P>0.05) between the groups, showing a degree of sedation grade 3 on the Ramsay scale and a reduction in the pain control score on the Feline Grimace Scale, without hemodynamic changes within the monitored clinical parameters.